3β, 6β-dichloro-5-hydroxy-5α-cholestane facilitates neuronal development through modulating TrkA signaling regulated proteins in primary hippocampal neuron - Hannan, Md. Abdul (Sci Rep, 2019)
Potentiating neuritogenesis through pharmacological intervention might hold therapeutic promise in neurodegenerative disorders and acute brain injury. Here, we investigated the novel neuritogenic potentials of a steroidal chlorohydrin, 3β, 6β-dichloro-5-hydroxy-5α-cholestane (hereafter, SCH) and the change in cellular proteome to gain insight into the underlying mechanism of its neurotrophic activity in hippocampal neurons. Morphometric analysis showed that SCH promoted early neuronal differentiation, dendritic arborization and axonal maturation. Proteomic and bioinformatic analysis revealed that SCH induced upregulation of several proteins, including those associated with neuronal differentiation and development. Immunocytochemical data further indicates that SCH-treated neurons showed upregulation of Hnrnpa2b1 and Map1b, validating their proteomic profiles. In addition, a protein-protein interaction network analysis identified TrkA as a potential target connecting most of the upregulated proteins. The neurite outgrowth effect of SCH was suppressed by TrkA inhibitor, GW441756, verifying TrkA-dependent activity of SCH, which further supports the connection of TrkA with the upregulated proteins. Also, the computational analysis revealed that SCH interacts with the NGF-binding domain of TrkA through Phe327 and Asn355. Collectively, our findings provide evidence that SCH promotes neuronal development via upregulating TrkA-signaling proteins and suggest that SCH could be a promising therapeutic agent in the prevention and treatment of neurodegenerative disorders.